Editorial (2011)
“We envisage our role as building a culture of significant possibility, that is, a culture where beliefs and choices are both context-bound and transformative, and where discourses and practices are situated somewhere between dominant and ideal realities.” I am delighted to present this new number of our journal. With this version we start the second decade of our publication and surely this will bring new challenges. The quote above, taken from the work by Vieira and Alfredo Moreira, perfectly fits the philosophy and policies we have built in PROFILE during the time we have been working in its publication. The editorial team, our reviewers, contributors and authors have joined efforts and provided support to maintain our publication because we also envisage our role as community builders. We believe in the importance of circulating our reflections and investigations through publishing. To do so, we have engaged in collaborative endeavours and received insights from advisors and our readership.